1992
DOI: 10.4049/jimmunol.148.12.3687
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous antigens induce in vivo tolerance selectively in IL-2- and IFN-gamma-producing (Th1) cells.

Abstract: As a model for understanding in vivo immune responses, we have exposed mice to aqueous haptenated-protein Ag, and examined immune responses to subsequent immunization with Ag in adjuvant. Pretreating mice with soluble, TNP-conjugated Ag induces selective nonresponsiveness to Ag for both humoral and cell-mediated immune functions. Specific T cell proliferation in response to Ag is inhibited, and Ag-induced secretion of the lymphokines IL-2 and IFN-gamma, but not IL-4, is reduced. B cell responses after pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Helper T cells are the important immune cells mediating inflammatory response [14], which can be divided into Th1 and Th2 cells that exert different immune effects [15,16]. Th1 cells are mainly dependent on IL-2 and IFN-γ [17], induce the macrophage-dependent immune response, enhance the toxic effect of natural killer (NK) cells, and mediate hypersensitivity reaction to cause tissue injury [18]. Th2 cells mainly secrete IL-4 and IL-10, which can promote the IgE-mediated hypersensitivity reaction and humoral immune response [19].…”
Section: Discussionmentioning
confidence: 99%
“…Helper T cells are the important immune cells mediating inflammatory response [14], which can be divided into Th1 and Th2 cells that exert different immune effects [15,16]. Th1 cells are mainly dependent on IL-2 and IFN-γ [17], induce the macrophage-dependent immune response, enhance the toxic effect of natural killer (NK) cells, and mediate hypersensitivity reaction to cause tissue injury [18]. Th2 cells mainly secrete IL-4 and IL-10, which can promote the IgE-mediated hypersensitivity reaction and humoral immune response [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discovered that peripheral inflammation is related to the peripheral T lymphocytes-secreted cytokines [ 12 , 13 ]. Th1 and Th2 are the two important subsets of Th cells, Th1 cells mainly secrete the pro-inflammatory cytokines to participate in macrophage activation for mediating cellular immunity [ 14 , 15 ], such as interleukin-6 (IL-6) [ 16 ], Interferon-γ (IFN-γ) [ 17 ]. By contrast, Th2 cells mainly secrete inhibitory cytokines like IL-4 and IL-10 [ 18 , 19 ] to mediate humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β) (26), and (iii) dysregulation between T h 1 and T h 2 cells (10). Considering the third possibility, it has been reported that T h 1 cells are more likely to be anergized than T h 2 cells (27). Therefore, oral tolerance has been shown to reflect preferential activation of T h 2 cells with subsequent downregulation of T h 1 responses (28).…”
Section: Discussionmentioning
confidence: 99%